Physical fitness in basketball players: a systematic review - Mancha-Triguero, D.; Garcia-Rubio, J.; González-Calleja, J.; Ibanez, S. J. (The Journal of Sports Medicine and Physical Fitness, 2019)
INTRODUCTION: Physical fitness is a performance factor that is characterized by its ability to be assessed using closed tests. Among the existing tests today, there are no data on which are the most optimal ones for the sport for which they are applied. Tests of a generic nature are widely used regardless of the sample of players or the sport to which is being referred as they allow to compare the performance among athletes. In spite of this, it is necessary to identify and develop specific tests of physical fitness for each sport. Thus, the main purpose of this review on physical fitness in basketball players was to identify and group the different tests described in the literature up until November 2018. EVIDENCE ACQUISITION: A literature search was conducted in the different data base to systematically ascertain the most commonly used tests for assessing physical fitness in basketball players. A total of 40 articles were selected, after passing the selection and exclusion criteria. EVIDENCE SYNTHESIS: Finally, they were classified according to the tests assessed in each document. The capacities more frequently studied in literature are jump (N.=21) aerobic capacity (N.=17) and anaerobic capacity (N.=16). On the contrary, the least common evaluated capacities are speed and agility (N.=14). CONCLUSIONS: The results and discussion showed that few specific tests are used to assess this quality in athletes. The analyzed bibliography reveals the lack of design and use of specific tests to highlight the qualities involved in the targeted sport.